Theimpactofbreastcanceronwomen'sself-image (ModaPalavra e-periódico, 2020)
Thisarticleexaminestheimpactofthesideeffectsofbreastcancertreatmentonwomen'sself-image.Qualitativeanddescriptiveresearchwasused,complementedwithfieldresearchwiththreewomenwithbreastcancerasasample.Afteranalyzingthedata,itwaspossibletoverifythatthereareimpactsonwomen'sself-image,especiallywhenthesideeffectsofthetreatmentsbegintobefelt
Keywords: self-image; self-esteem; breast cancer; women